2015
DOI: 10.1002/2014jb011714
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution magnetic signature of active hydrothermal systems in the back‐arc spreading region of the southern Mariana Trough

Abstract: High-resolution vector magnetic measurements were performed on five hydrothermal vent fields of the back-arc spreading region of the southern Mariana Trough using Shinkai 6500, a deep-sea manned submersible. A new 3-D forward scheme was applied that exploits the surrounding bathymetry and varying altitudes of the submersible to estimate absolute crustal magnetization. The results revealed that magnetic-anomaly-derived absolute magnetizations show a reasonable correlation with natural remanent magnetizations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 67 publications
2
18
0
Order By: Relevance
“…Thus, to resolve magnetic anomalies at the scale and depth of the hydrothermal systems and to counteract the natural decay of the magnetic field with depth, near‐seafloor data collected by deep‐submergence vehicles such as autonomous underwater vehicles (AUVs) or remotely operated vehicles (ROVs) are required. Near‐seafloor high‐resolution magnetic surveys of basalt‐hosted hydrothermal vent sites at MORs or back‐arc basins (e.g., Caratori Tontini et al, ; Caratori Tontini et al, ; Fujii et al, ; Tivey et al, ; Tivey & Dyment, ; Tivey & Johnson, ) and at submarine arc volcanoes (Caratori Tontini, Davy, et al, ; Caratori Tontini et al, , Honsho et al, ; Szitkar et al, ) have revealed well‐defined magnetic “burnholes,” that is, discrete zones of reduced crustal magnetization in and around areas of active and extinct vent sites, inferred to represent hydrothermal upflow zones.…”
Section: Geophysical Surveysmentioning
confidence: 99%
“…Thus, to resolve magnetic anomalies at the scale and depth of the hydrothermal systems and to counteract the natural decay of the magnetic field with depth, near‐seafloor data collected by deep‐submergence vehicles such as autonomous underwater vehicles (AUVs) or remotely operated vehicles (ROVs) are required. Near‐seafloor high‐resolution magnetic surveys of basalt‐hosted hydrothermal vent sites at MORs or back‐arc basins (e.g., Caratori Tontini et al, ; Caratori Tontini et al, ; Fujii et al, ; Tivey et al, ; Tivey & Dyment, ; Tivey & Johnson, ) and at submarine arc volcanoes (Caratori Tontini, Davy, et al, ; Caratori Tontini et al, , Honsho et al, ; Szitkar et al, ) have revealed well‐defined magnetic “burnholes,” that is, discrete zones of reduced crustal magnetization in and around areas of active and extinct vent sites, inferred to represent hydrothermal upflow zones.…”
Section: Geophysical Surveysmentioning
confidence: 99%
“…Zealand showed that hydrothermal alteration of magnetic minerals is the most important 68 mechanism for creating zones of weak magnetization rather than by thermal 69 demagnetization processes (Hochstein and Soengkono, 1997). In the seafloor realm, 70 weak magnetization zones were observed in both active and extinct vent areas, also 71 suggesting that differences in the thermal environment do not significantly affect 72 magnetic anomalies (Fujii et al, 2015;Tivey and Johnson, 2002). Another explanation 73 for zones of weak magnetic response is the accumulation of thick hydrothermal deposits, 74 which may result in an apparent magnetic low due to the increased distance between the 75 measurement point and the underlying magnetized basalt (Szitkar et al, 2014a).…”
Section: Wooldridgementioning
confidence: 99%
“…The location and spatial extent of 46 hydrothermal activity are difficult to constrain; however, studies of near-seafloor 47 magnetic field can highlight these features because crustal magnetic minerals can be 48 destroyed or created by hydrothermal processes. Reduced magnetization associated with 49 hydrothermal deposits was widely observed in both the active and inactive lava-hosted 50 hydrothermal fields in varied tectonic settings, including: the hydrothermal site TAG 51 (Trans-Atlantic Geotraverse) and the 4°48′S fields of the Mid-Atlantic Ridge (MAR; 52 Tivey and Dyment., 2010;Tivey et al, 1993Tivey et al, , 1996Tivey et al, , 2003, the Main Endeavour Field and 53 Raven Field of the Juan de Fuca Ridge (JFR; Tivey and Johnson, 2002;Tivey et al, 2014), 54 a site on the Southwest Indian Ridge (Zhu et al, 2010), back-arc-type sites of the 55 Southern Mariana Trough (Fujii et al, 2015;Nakamura et al, 2013), the Hakurei Field 56 within a caldera of the Izu-Ogasawara arc-back-arc volcano (Honsho et al, 2013), and 57 the Brothers Field within a caldera of the Kermadec intraoceanic arc volcano 58 (Caratori- Tontini et al, 2012). 59…”
Section: Introduction 42mentioning
confidence: 99%
“…Near‐seafloor magnetic surveys provide a unique method for mapping hydrothermal alteration in the submarine environment [e.g., Tivey and Johnson , ; Tivey and Dyment , ; Tivey et al , ; Honsho et al , ; Fujii et al , ; Szitkar et al , , ]. Young oceanic crust is characterized by strong magnetization caused by magnetite and titanomagnetite minerals within the lavas.…”
Section: Discussionmentioning
confidence: 99%